2011
DOI: 10.1159/000328719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Progesterone as a Tocolytic and in Maintenance Therapy during Preterm Labor

Abstract: Aims: To assess the efficacy of vaginal micronized natural progesterone as a tocolytic and in maintenance therapy during threatened preterm birth. Methods: Eighty-three women with symptoms of threatened preterm birth were either randomized to study groups receiving tocolytic treatment combined with intravaginal micronized natural progesterone (200 mg daily) or to a control group receiving only tocolysis. Results: Micronized natural progesterone treatment resulted in a prolonged latency period of 32.1 ± 17.8 ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
3
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 30 publications
7
53
3
9
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27][28][29][30] But there are few studies regarding role of progesterone in threatened PTL. [34][35][36][37][38][39] Most of the studies compared the effect of progesterone as a maintainance tocolytic with placebo after initial tocolysis with other agents. There are very few studies compairing the different routes of use of progeterone.…”
Section: Results and Analysismentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30] But there are few studies regarding role of progesterone in threatened PTL. [34][35][36][37][38][39] Most of the studies compared the effect of progesterone as a maintainance tocolytic with placebo after initial tocolysis with other agents. There are very few studies compairing the different routes of use of progeterone.…”
Section: Results and Analysismentioning
confidence: 99%
“…In various studies improvement in birth weight ranged from 290-490 gms. 11,[13][14][15]18 NICU admission were also less in study group(14% vs 24%) with shorter nursery stay(7.71 vs 8.41 days).Neonatal complications like RDS, sepsis, mechanical ventilation were also less in study group. There was one case of neonatal death in Group II.…”
Section: Discussionmentioning
confidence: 72%
“…Results are similar as reported in literature though progesterone, dose and route are different in various studies. 11,[13][14][15][16] Borna et al reported difference in prolongation of pregnancy by 11.5 days while Gargari et al reported it to be 2.6 weeks. Bomba-Opon et al observed a significant reduction in delivery before 34 weeks with vaginal progesterone (9.8% in progesterone group versus 35.3% in control group; p = 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…Un par de estudios recientes apoyan el uso de progesterona como tocolítico de mantención luego de la frenación aguda con otro fármaco (8,9). Sin embargo, la evidencia es insuficiente para recomendar el uso progesterona como tocolítico de mantención en pacientes con trabajo de parto prematuro, justificando la necesidad de más estudios, de buena calidad, para demostrar la eficacia de progesterona micronizada vía oral para la prolongación del embarazo en los casos de parto prematuro frenado.…”
Section: A Relevancia De La Investigaciónunclassified
“…Realizado entre octubre 2010 y abril 2012. El cál-culo del tamaño muestral se efectuó asumiendo 12 días de desviación estándar, basados en los datos obtenidos en otro estudio que evaluó tocolisis de mantención (9). Así se determinó que era necesario reclutar 42 pacientes por grupo para detectar 12 días de diferencia en tiempo ganado de embarazo, con un nivel de significación de 5% y poder estadís-tico de 80%.…”
Section: B El Estudio (1)unclassified